Using concept mapping to identify policy options and interventions towards people-centred health care services: a multi stakeholders perspective - Christine Cécile Leyns; Jan De Maeseneer; Sara Willems (BMC, 2018)
Abstract Background People-centred health care (PCC) services are identified by the WHO as important building blocks towards universal health coverage. In 2016 the WHO formulated a comprehensive framework on integrated PCC services based on an international expert consultation. Yet, expert opinions may fail to recognize the needs of all health system stakeholders. Therefore, a consultation method that includes the health workforce and laypersons, can be instrumental to elaborate this framework more in-depth. This research sought to identify participants' perspectives on policy options and interventions to achieve people-centred health care services from a multi stakeholder perspective. Methods Study participants, both laypersons and health professionals, were recruited in Belgium. A total of 53 participants engaged in one of the seven concept mapping workshops. In this workshop the concept mapping methodology developed by Trochim, a highly structured qualitative group method for brainstorming and idea sharing, was used to generate and structure participants´ perspectives on what is needed to achieve PCC services. The method was validated using the WHO framework. Results The seven workshops together resulted in 452 different statements that were structured in a framework forming 35 clusters and four overarching domains. The four domains with their most prominent clusters were: (1) governance & policy with intersectoral health policies and affordable health for all; (2) health workforce with excellent communication skills, appreciation of health literacy challenges and respectful attitude based on cultural self-awareness; (3) integrated health services with a greater emphasis on prevention, health promotion and the availability of health education and (4) patient, person and community empowerment and participation with support for informal care, promotion of a healthy lifestyle and contextualised health education. Additionally, this study generated ideas that fitted into every single approach described in the WHO framework. Discussion and conclusion This study shows that in order to achieve PCC a participative approach involving all stakeholders at all levels is needed. The concept mapping process is one of these approaches that brings together diverse stakeholders and foments their egalitarian and respectful participation. The framework that resulted from this study can inform future debate regarding planning, implementation and monitoring of PCC.